World futures through RT’s eyes: multimodal dataset and interdisciplinary methodology - Wilson, Anna; Pavlova, Irina; Payne, Elinor; Burenko, Ilya; Uhrig, Peter (Frontiers in Communication, 2024)
There is a need to develop new interdisciplinary approaches suitable for more complete analysis of multimodal data. Such approaches need to go beyond case studies and leverage technology to allow for statistically valid analysis of the data. Our study addresses this need by engaging with the research question of how humans communicate about the future for persuasive and manipulative purposes, and how they do this multimodally. It introduces a new methodology for computer-assisted multimodal analysis of video data. The study also introduces the resulting dataset featuring annotations for speech (textual and acoustic modalities), and gesticulation and corporal behaviour (visual modality). To analyse and annotate the data and develop the methodology the study engages with twenty-three 26minute episodes of the show "SophieCo Visionaries" broadcast by RT (formerly 'Russia Today').